FTIR Spectroscopic Analysis in Comparison with Acoustical Nature in Mono, Di and Tri Methyl Substituent Liquid Mixtures. (March 2019) - Sarma Nori, Timmeswara; Babavali, Sk Fakruddin; Srinivasu, Ch
Abstract: FTIR spectroscopic study is a useful method to identify the functional groups and to know the nature of bond between different liquid mixtures. In the present case it is paid much interest towards the variation in the acoustical parameters with the bond strength in binary liquid mixtures. The work was keenly performed to study the acoustical variations bond strength with methyl group substituent in a liquid mixture containing aniline + toluene (mono methyl group), aniline + o-xylene (di methyl group) and aniline + mesitylene (tri methylgroup) at ratio of different mole fractions. Ultrasonic velocities, and densities in binary liquid mixtures containing (aniline + toluene), (aniline + o-xylene) and (aniline + mesitylene) along with their acoustical parameters are studied at room temperature (T = 303.15 K) with different mole fractions of aniline. The results obtained are compared and discussed in terms of molecular associations between the component molecules in terms of bond strength (C-N, C-H & N-H) of the binary liquid mixtures. The results thus derived are verified by using Hooke's law.